Pengolahan Makanan Ringan Corndog Sosis sebagai Peluang Bisnis Usaha Kecil - Khairani, Iftahul; Efrilia, Celline; Badres, Shofi Azzahra; Nurandi, Amelia Putri (Masyarakat Ekonomi Syariah Bogor, 2024)
Corndog is a food or snack that is included in Korean Street Food, Corndog is a food that consists of several ingredients, namely flour, sausage, mozzarella cheese, potatoes, chocolate, green tea and sauce. The melted mozzarella cheese is what makes it attractive to customers and besides that, there are many various variants that can meet customer desires. This research aims to see the extent of business results obtained by selling typical corndog food in the research area and to find out the processing process for making delicious corndog food so that it is suitable for sale and consumption by the public. The method used in this corndog sausage business research is quantitative and qualitative. And from sales made by sellers there is a profit of 21% per day in 1 sale on October 17 2023.